2008
DOI: 10.1128/mcb.00611-08
|View full text |Cite
|
Sign up to set email alerts
|

CD40 Induces Antigen Transporter and Immunoproteasome Gene Expression in Carcinomas via the Coordinated Action of NF-κB and of NF-κB-Mediated De Novo Synthesis of IRF-1

Abstract: Cancer cells may evade immune surveillance as a result of defective antigen processing and presentation. In this study, we demonstrate that CD40 ligation overcomes this defect through the coordinated action of the transcription factors NF-B and interferon regulatory factor 1 (IRF-1). We show that unlike interferon signaling, which triggers the STAT1-mediated transcriptional activation of IRF-1, the ligation of CD40 in carcinomas induces the rapid upregulation of IRF-1 in a STAT1-independent but NF-B-dependent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
11

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 72 publications
1
34
0
11
Order By: Relevance
“…HEK 293 cells (1.5 3 10 5 cells/well in a 12-well plate) were transfected with 50 ng pIFN-b/Luc and 50 ng of a Renilla plasmid and plasmids expressing CD40WT, CD40mT2/T3, CD40 mT2/T3/T6, or HA-p52 by using Lipofectamine (Invitrogen) in Opti-MEM medium (Invitrogen), according to the manufacturer's instructions. Following a 10-h incubation with the transfection mixture, the medium was changed to DMEM supplemented with 10% FCS, and Luciferase and Renilla values were measured 24 h later as described previously (15).…”
Section: Reporter Assaysmentioning
confidence: 99%
See 2 more Smart Citations
“…HEK 293 cells (1.5 3 10 5 cells/well in a 12-well plate) were transfected with 50 ng pIFN-b/Luc and 50 ng of a Renilla plasmid and plasmids expressing CD40WT, CD40mT2/T3, CD40 mT2/T3/T6, or HA-p52 by using Lipofectamine (Invitrogen) in Opti-MEM medium (Invitrogen), according to the manufacturer's instructions. Following a 10-h incubation with the transfection mixture, the medium was changed to DMEM supplemented with 10% FCS, and Luciferase and Renilla values were measured 24 h later as described previously (15).…”
Section: Reporter Assaysmentioning
confidence: 99%
“…The p52 Ab was purchased from Cell Signaling Technology, the IRF7 from Acris and the actin Ab from Sigma-Aldrich. Immunoblotting was performed as described previously (15).…”
Section: Abs and Immunoblottingmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, they concluded that LMP-1 could increase the antigen presentation of both TAP-1 and TAP-2 through NFjB. Moschonas et al (2003) discovered that the CD40 ligand could induce antigen presentation and related gene expression (TAP-1, TAP-2, LMP-2, LMP-10 and tapasin). These gene promoters all contained NF-jB binding regions.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro, vIL-10 can down-regulate the expression of TAP-1, TAP-2, LMP-2, LMP-7 and HLA-I in CNE-2 cells (data is not shown). The expression of TAP-1, TAP-2, LMP-2, LMP-7 and HLA-I involves the activation of NF-jB and its recruitment to the promoter elements proximal to the gene transcription start sites (Moschonas et al 2003;Molinero et al 2004).…”
Section: Introductionmentioning
confidence: 99%